2019
DOI: 10.1111/1475-6773.13128
|View full text |Cite
|
Sign up to set email alerts
|

Do timely mental health services reduce re‐incarceration among prison releasees with severe mental illness?

Abstract: Objective To examine whether the receipt of timely mental health services is associated with changes in criminal justice interactions. Data Sources We used linked administrative data from Medicaid, mental health, and criminal justice settings in Washington State for persons with severe mental illness released from prison (n = 3086). Study Design We estimate local and average treatment effects to examine measures of criminal justice use in the year following release as a function of timely mental health service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“… Linked data to county criminal justice information systems containing information about all individuals in contact with criminal justice. Domino et al (2019) [ 35 ] USA 2006–2007 12 months Retrospective cohort; N =3086 ( n =871, referral group; n =2215, non-referral group) All adults with severe mental illness who were released from prison during the first two years of an expedited Medicaid policy 57% in the referral group and 53% in the non-referral group had alcohol or drug use disorder. Medicaid funded inpatient and outpatient mental health services vs. standard public mental health services (linked data).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Linked data to county criminal justice information systems containing information about all individuals in contact with criminal justice. Domino et al (2019) [ 35 ] USA 2006–2007 12 months Retrospective cohort; N =3086 ( n =871, referral group; n =2215, non-referral group) All adults with severe mental illness who were released from prison during the first two years of an expedited Medicaid policy 57% in the referral group and 53% in the non-referral group had alcohol or drug use disorder. Medicaid funded inpatient and outpatient mental health services vs. standard public mental health services (linked data).…”
Section: Resultsmentioning
confidence: 99%
“…Specific criminal justice outcomes varied. Six studies reported reimprisonment [ 36 , 37 , 39 , 44 , 46 ], three studies reported re-arrest [ 34 , 38 , 40 ], two studies reported recidivism [ 41 , 43 ], one study reported reconviction [ 45 ], and two studies reported both re-arrest and reimprisonment [ 35 , 42 ]. Measurement of primary outcomes also varied, including analysing associations of criminal justice involvement following exposure to community mental health services after controlling for covariates [ 34 , 35 , 38 , 39 , 44 ], measuring rates of criminal justice involvement [ 40 , 42 , 43 ], reporting time-to-event of criminal justice involvement [ 42 , 45 , 46 ], measuring the timing and frequency of criminal justice involvement following exposure to community mental health services [ 41 ], and the number of days spent in prison following exposure to community mental health services (Table 1 ) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the literature [31], we also found that the burden of psychiatric illness in this cohort was substantial, especially for females. Previous research has highlighted the benefits of targeted support for people with serious mental illness transitioning from prison to the community [32], given that this group is also typically at higher risk of reincarceration [33].…”
Section: Discussionmentioning
confidence: 99%
“…(4) Adaptability factors. When students get access to the campus, they are prone to psychological imbalance in the face of new living environment and learning style, further causing mental dysfunctions (Domino, Gertner, Grabert et al, 2019).…”
Section: Analysis Of Mental Health Factorsmentioning
confidence: 99%